2020
DOI: 10.1002/wrna.1613
|View full text |Cite
|
Sign up to set email alerts
|

Fatal attraction: The roles of ribosomal proteins in the viral life cycle

Abstract: Upon viral infection of a host cell, each virus starts a program to generate many progeny viruses. Although viruses interact with the host cell in numerous ways, one critical step in the virus life cycle is the expression of viral proteins, which are synthesized by the host ribosomes in conjunction with host translation factors. Here we review different mechanisms viruses have evolved to effectively seize host cell ribosomes, the roles of specific ribosomal proteins and their posttranslational modifications on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 150 publications
(210 reference statements)
0
9
0
Order By: Relevance
“…In addition, we observed that host proteins that are targeted by M protein form a PPI network centered on ribosomal proteins. As we all know, the function of the ribosome is mainly responsible for translation regulation within the host, and many researchers have found that ribosomes play an indispensable role in the life cycle of viruses (Li, 2019;Miller et al, 2021). Therefore, we speculated that SADS-CoV M protein may create conditions for viral translation by targeting ribosomal proteins in the host, which deserve further studies.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, we observed that host proteins that are targeted by M protein form a PPI network centered on ribosomal proteins. As we all know, the function of the ribosome is mainly responsible for translation regulation within the host, and many researchers have found that ribosomes play an indispensable role in the life cycle of viruses (Li, 2019;Miller et al, 2021). Therefore, we speculated that SADS-CoV M protein may create conditions for viral translation by targeting ribosomal proteins in the host, which deserve further studies.…”
Section: Discussionmentioning
confidence: 91%
“…At present, more and more researchers pay attention to the relationship between the ribosome and the virus. Ribosomal proteins play an important role in the life cycle of viruses, such as promoting virus translation, participating in virus assembly and replication, and acting as virus receptors (Li, 2019;Dong et al, 2021;Miller et al, 2021). RPL18 belongs to the ribosomal 60s subunit, and some studies have shown that it is involved in ribosome assembly.…”
Section: Discussionmentioning
confidence: 99%
“…rRNAs are the main effectors of ribosome dynamics during mRNA decoding, peptide bond formation, and translation ( Erales et al, 2017 ). In addition to being components of ribosomes, RPs play an important role in ribosome biogenesis, and they regulate many fundamental life processes, including cell cycle, cell proliferation, apoptosis, tumor development, genome integrity and development, and so on ( Li, 2019 ; Miller et al, 2021 ).…”
Section: Viruses Hijack Ribosomes To Complete Viral Protein Translationmentioning
confidence: 99%
“…EBV has a complex life cycle, showing different cellular tropisms depending on the stage of infection. At least five different stages have been described as being part of the viral life cycle: lytic infection, latency III, latency II, latency I/0, and lytic reactivation [108][109][110].…”
Section: Epstein-barr Virus (Ebv)mentioning
confidence: 99%